JUSTIFICATION OF GEOINFORMATION SYSTEM ON LAND SOILS QUALITY MONITORING - Moskalenko, А. А. (Землеустрій, кадастр і моніторинг земель, 2012)
In article the making components necessary for for creation of system of geoinformation monitiring of soil and development of conceptual model of complex GIS of a qualitative condition of soil are analyze. Components of bank of geospatial data of monitiring of quality of lands of agricultural purpose are proved.